Enhanced catalytic degradation of acetaminophen using magnesium oxide-infused clay with ultrasonic activation of hydrogen peroxide - Roshana Rashidi; Seyed Hamed Meraji; Amin Mahmoudi; Ali Mohammad Sanati; Bahman Ramavandi (Arabian Journal of Chemistry)
In this study, clay modified with magnesium oxide (MgO) was used as a catalyst for the degradation of acetaminophen in wastewater, activated by hydrogen peroxide (H2O2) and ultrasonic waves. Characterization of the Clay-MgO catalyst was conducted using TGA, XRD, BET, SEM, FTIR, XRF, and EDX, revealing functional groups capable of activating H2O2. The crystalline catalyst, synthesized at 500 °C, had a surface area of 30 m2/g. Optimal conditions for acetaminophen removal, achieving 75 % efficiency, were pH 8, 3 g/L catalyst, 0.2 mL/100 mL H2O2, and 60 min of contact time. In distilled water, mineralization of acetaminophen was 42 %, while actual wastewater showed 18 %. Hydroxyl radicals played a significant role in the degradation process. The catalyst was tested for reuse up to six times and maintained a high efficiency of over 53 % in five stages. Radical scavenger studies confirmed the importance of hydroxyl radicals in the degradation kinetics, which followed pseudo-first-order (R2 > 0.96) and Langmuir-Hinshelwood (R2 = 0.95) models. The catalyst also demonstrated efficient acetaminophen removal in complex solutions, including seawater. This MgO-modified clay shows promise as an effective catalyst for the degradation of pharmaceutical pollutants through hydrogen peroxide activation, maintaining stability and reusability across multiple cycles.